The influence of trunk forward inclination on knee biomechanics and myoelectricity during sidestep cutting - Shi, X.; Wang, H.; Xie, D.; Liu, H.; Li, X.; Wang, H.; Ma, B. (Medicina dello Sport, 2023)
BACKGROUND: Trunk motion control may be an important factor affecting the risk of anterior cruciate ligament (ACL) injury by changing knee joint load during dynamic motion, there has been few studies investigating the influence of it on knee joint during sidestep cutting currently, and it has not been studied whether asymmetry between the dominant and non-dominant lower limbs in different trunk motion states during sidestep cutting. The objective of this study was to identify the leg laterality during sidestep cutting in trunk forward inclination state and to explore whether trunk forward inclination could reduce ACL injury risk.